Bài 2: (1,5 điểm)
Cho biểu thức $P=\left ( \frac{1}{x-\sqrt{x}}+\frac{1}{\sqrt{x}-1} \right ):\frac{\sqrt{x}}{x-2\sqrt{x}+1}$ (với $x> 0;x\neq 1$)
a. Rút gọn biểu thức P
b. Tìm hiểu các giá trị của $x$ để $P>\frac{1}{2}$
Bài Làm:
a. $P=\left ( \frac{1}{\sqrt{x}(\sqrt{x}+1)}+\frac{\sqrt{x}}{\sqrt{x}(\sqrt{x}-1)} \right ):\frac{\sqrt{x}}{x-2\sqrt{x}+1}$
$=\left ( \frac{1}{\sqrt{x}(\sqrt{x}-1)}+\frac{\sqrt{x}}{\sqrt{x}(\sqrt{x}-1)} \right ).\frac{(\sqrt{x}-1)^{2}}{\sqrt{x}}$
$=\frac{1+\sqrt{x}}{\sqrt{x}(\sqrt{x}-1)}.\frac{(\sqrt{x}-1)^{2}}{\sqrt{x}}=\frac{(\sqrt{x}+1)(\sqrt{x}-1)}{\sqrt{x}.\sqrt{x}}=\frac{x-1}{x}$
b. Với $x>0;x\neq 1$ thì $\frac{x-1}{x}>\frac{1}{2}\Leftrightarrow 2(x-1)>x\Leftrightarrow x>2$
Vậy với $x>2$ thì $P> \frac{1}{2}$